Polyester and molded article thereof
By controlling the proportion of repeating units in polyester, the problem of insufficient heat resistance of existing polyester products is solved, and the dyeing ability and mechanical strength are improved, achieving multiple performance improvements of polyester, which are suitable for environmental protection and industrial needs.
Patent Information
- Application Number
- CN202311271957.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The existing polyester products have shortcomings in terms of heat resistance, or the dyeing ability and mechanical strength decrease when improving heat resistance.
By controlling the proportion of repeating units in the polyester within a specific range (the weight ratio of the second repeating unit to the third repeating unit is 0.100 to 0.490), polyester having both ideal heat resistance, good dyeing ability and mechanical strength is obtained.
The comprehensive improvement of polyester in terms of heat resistance, dyeing ability and mechanical strength has been achieved, meeting the industry's multiple needs for polyester, and the recycling of polyester can be used as raw materials, in line with environmental protection trends.
Smart Images

Figure BDA0004475808540000021 
Figure BDA0004475808540000022 
Figure BDA0004475808540000023
Abstract
Description
Technical Field
[0001] The present application relates to a polyester composition, particularly a polyester composition and a molded product thereof, but is not limited thereto. Background Art
[0002] Polymers with ester functional groups on the main chain are collectively called polyesters. They have the characteristics of light weight, impact resistance, not easy to break and high transparency. They can be used in a variety of daily necessities packaging, such as plastic bottles or food packaging films.
[0003] Specifically, the common polyester may be polybutylene terephthalate (PBT), polybutylene isophthalate (PBI), polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polypropylene terephthalate (PPT), polypropylene isophthalate (PPI), polytrimethylene terephthalate (PTT), thermoplastic polyether ester elastomer (TPEE) or aliphatic polyalkylene phenylene esters or polyalkylene phenylene ester ether. Summary of the invention
[0004] The inventor of the present application has found that the finished products prepared by using the polyester of the prior art often have poor heat resistance, or have heat resistance, but their dyeing ability and / or mechanical strength are reduced. Based on this, the inventor of the present application has found after research that by controlling the ratio of repeating units in the polyester within a specific range, a polyester having both ideal heat resistance and good dyeing ability and mechanical strength can be obtained, thereby achieving the purpose of obtaining a polyester that meets the needs of the industry.
[0005] Specifically, the present application provides a polyester on one hand, which comprises: a first repeating unit, which is represented by the following formula (i): Among them, R1 is C6 to C 16An aromatic hydrocarbon group; and a repeating unit derived from a diol, wherein the repeating unit derived from the diol comprises a second repeating unit, a third repeating unit and an aliphatic cycloalcohol residue; wherein the second repeating unit is represented by the following formula (ii), and the third repeating unit is represented by the following formula (iii): * represents a connecting bond; and, the polyester is analyzed by aminolysis, and the weight ratio of the second repeating unit to the third repeating unit is 0.100 to 0.490.
[0006] In one or more embodiments, the aliphatic cycloalcohol residue is derived from an aliphatic cyclodiol having a boiling point of not less than 280° C. at room temperature and pressure.
[0007] In one or more embodiments, the aliphatic cyclic alcohol residue comprises an isosorbide residue, a cyclohexanedimethanol residue, a tricyclodecane dimethanol residue, or a combination thereof.
[0008] In one or more embodiments, the weight ratio of the second repeating unit to the third repeating unit is 0.100 to 0.484.
[0009] In one or more embodiments, the aliphatic cycloalcohol residue comprises a structure of formula (iv): * indicates a connection key.
[0010] In one or more embodiments, the weight ratio of the second repeating unit to the third repeating unit is 0.246 to 0.484.
[0011] In one or more embodiments, the aliphatic cycloalcohol residue comprises a structure of formula (v): * indicates a connection key.
[0012] In one or more embodiments, the weight ratio of the second repeating unit to the third repeating unit is 0.102 to 0.481.
[0013] In one or more embodiments, the aliphatic cycloalcohol residue comprises a structure of formula (vi): * indicates a connection key.
[0014] In one or more embodiments, the weight ratio of the second repeating unit to the third repeating unit is 0.164 to 0.484.
[0015] In one or more embodiments, the content of the second repeating unit is no more than 3 wt. % of the total weight of the polyester.
[0016] In one or more embodiments, it has a glass transition temperature (T g ) is greater than 90°C.
[0017] In one or more embodiments, it is prepared from a recycled polyester via a transesterification reaction.
[0018] Another aspect of the present application provides a molded product, which is formed from the polyester as described above.
[0019] The polyester of the present application has ideal heat resistance as well as good dyeing ability and mechanical strength, thereby achieving the purpose of producing polyester that meets the needs of the industry. In addition, the present application can further use recycled polyester as raw material to achieve the advantage of being in line with environmental protection trends. DETAILED DESCRIPTION
[0020] In order to make the description of the present application more detailed and complete, the following is an illustrative description of the implementation and specific embodiments of the present application, but this is not the only form of implementing or applying the specific embodiments of the present application. The various embodiments disclosed below can be combined or replaced with each other in beneficial situations, and other embodiments can be added to one embodiment without further recording or explanation. In the following description, many specific details will be described in detail so that the reader can fully understand the following embodiments; however, the embodiments of the contents disclosed in this application can be practiced without such specific details. In addition, in this specification and the scope of the attached patent application, unless the context otherwise states, "one" and "the" can also be interpreted as plural.
[0021] Although a series of operations or steps are used below to illustrate the method disclosed herein, the order shown in these operations or steps should not be construed as a limitation of the present application. For example, certain operations or steps can be performed in different orders or simultaneously with other steps. In addition, it is not necessary to perform all operations, steps, features to realize the embodiment of the present application. In addition, each operation or step described here can include several sub-steps or actions.
[0022] [Polyester]
[0023] On the one hand, the present application provides a polyester, which comprises: a first repeating unit, which is represented by the following formula (i): Among them, R1 is C6 to C 16 An aromatic hydrocarbon group; and a repeating unit derived from a diol, wherein the repeating unit derived from the diol comprises a second repeating unit, a third repeating unit and an aliphatic cycloalcohol residue; wherein the second repeating unit is represented by the following formula (ii), and the third repeating unit is represented by the following formula (iii): * represents a connecting bond. In addition, after aminolysis analysis of the polyester, the weight ratio of the second repeating unit to the third repeating unit is 0.100 to 0.490.
[0024] According to at least one embodiment of the present application, the polyester of the present application is polyethylene terephthalate (PET), poly trimethylene terephthalate (PTT) or polybutylene terephthalate (PBT); preferably, it is PET or PBT; more preferably, it is PET.
[0025] The C6 to C 16 Aromatic hydrocarbon groups, examples of which include but are not limited to phenylene, tolylene, naphthylene or anthracene; in some embodiments, R1 in the formula (i) of the first repeating unit is or a combination of the foregoing, wherein * represents a connecting bond.
[0026] The first repeating unit in the present application can be derived from a dibasic acid or a dibasic ester. The dibasic acid monomer comprises an aromatic dicarboxylic acid monomer, and examples thereof include but are not limited to terephthalic acid, isophthalic acid, phthalic acid, 2-methyl-1,4-phthalic acid, 1,4-naphthalene dicarboxylic acid or 2,6-naphthalene dicarboxylic acid. The dibasic ester can be an ester with a structure corresponding to the above-mentioned dibasic acid, and examples thereof include but are not limited to dimethyl terephthalate, diethyl terephthalate, dimethyl phthalate, diethyl phthalate, dimethyl isophthalate, diethyl isophthalate, 2-methyl-1,4-dimethyl phthalate, 1,4-dimethyl naphthalate or 2,6-dimethyl naphthalate.
[0027] According to at least one embodiment of the present application, the second repeating unit and the third repeating unit of the present application are derived from a diol, and the structure is as defined above. The inventor of the present application found that, through aminolysis analysis, when the weight ratio of the second repeating unit to the third repeating unit of the polyester of the present application is in a specific range, it can simultaneously have ideal heat resistance, good dyeing ability and mechanical strength, and thus can obtain the purpose of polyester that meets the needs of the industry. Specifically, through aminolysis analysis of the polyester of the present application, the weight ratio of the second repeating unit to the third repeating unit is 0.100 to 0.490, for example but not limited to 0.100, 0.150, 0.200, 0.250, 0.300, 0.350, 0.400, 0.450 or 0.490, or any value within the range formed by any two of the above values; preferably, the weight ratio of the second repeating unit to the third repeating unit of the polyester is 0.102 to 0.484, for example but not limited to 0.102, 0.150, 0.164, 0.190, 0.192, 0.197, 0.246, 0.289, 0.305, 0.330, 0.357, 0.407, 0.414, 0.481 or 0.484, or any value within the range formed by any two of the above values; more preferably, the weight ratio of the second repeating unit to the third repeating unit of the polyester is 0.102 to 0.481, 0.164 to 0.484, or 0.246 to 0.484. According to at least one embodiment of the present application, the source of the second repeating unit or the third repeating unit of the polyester of the present application can be generated during the preparation process, and can also be adjusted by post-addition.
[0028] According to at least one embodiment of the present application, the content of the second repeating unit of the polyester accounts for no more than 3wt.%, of the total weight of the polyester, for example, but not limited to no more than 3wt.%, no more than 2.5wt.%, no more than 2.0wt.%, no more than 1.5wt.%, no more than 1.0wt.% or no more than 0.5wt.%; preferably, the content of the second repeating unit of the polyester accounts for 2.83wt.%, 2.78wt.%, 2.47wt.%, 2.32wt.%, 1.97wt.%, 1.85wt.%, 1.75wt.%, 1.65wt.%, 1.17wt.%, 1.08wt.%, 0.96wt.%, 0.64wt.%, 0.57wt.%, 0.55wt.% or 0.4wt.% of the total weight of the polyester.
[0029] The "aminolysis analysis" of the present application refers to the quantitative analysis of the second repeating unit and the third repeating unit in the polyester; according to a preferred embodiment of the present application, the aminolysis analysis adopts an internal standard method, which is compared with the external standard method or the conventional method. 1 H-NMR ( 1 H-Nuclear magnetic resonance, 1 H-NMR) quantitative analysis is prone to errors (the reasons are explained in detail in the next paragraph), and the internal standard method can more accurately determine the content of the second repeating unit and the third repeating unit. The "internal standard method" is to add a substance with a known concentration and completely soluble in a solvent (such as but not limited to hexanediol used in this application) to the sample, called an internal standard substance (also referred to as an internal standard substance) as a comparison benchmark and used to compensate for errors and variability that may occur during the analysis process; when measuring, first determine the content of the internal standard substance in the sample, and then determine the content of the substance to be measured. The content of the substance to be measured can be calculated based on the ratio of the signal of the internal standard substance to the signal of the substance to be measured. Without being bound by a specific theory, the inventors of the present application have found that since the contents of the second repeating unit and the third repeating unit in the polyester of the present application are relatively low in the overall system (trace analysis), even if the differences in the processing and analysis conditions of the sample and the standard substance have been minimized, it may still have a significant impact on the quantitative results (such as the difference in injection conditions will directly affect the quantitative results); therefore, compared with the external standard method, it is more appropriate to use the internal standard method.
[0030] Different from the aforementioned internal standard method, when 1H-NMR is used to quantitatively analyze the polyester of the present application, the signal of the second repeating unit and the signal of the third repeating unit are easily affected by the signal of the terminal alcohol in the polyester to be tested and the signal of the cyclic polyester present in trace amounts, and all the aforementioned signals may cause the characteristic peaks on the hydrogen spectrum to be split into smaller characteristic peaks; in addition, except for the characteristic peak corresponding to the third repeating unit, the remaining characteristic peaks are particularly close and similar, and therefore are easily regarded as noise; and if other characteristic peaks such as residues of butanediol, residues of cyclohexanedimethanol, residues of tricyclodecane dimethanol, or residues of isosorbide are included, it is easier for the characteristic peaks to interfere with each other and overlap in the spectrum, causing the spectrum to be too complex and difficult to judge. In addition, the integral of the spectrum will also have obvious differences due to the adjustment of the waveform during detection and the different cutting positions, and the characteristic peaks will also be different due to the different selection of chemical shift ranges; in addition, since the content of the second repeating unit and the third repeating unit is very low, the aforementioned negative impact on the quantitative results will be increased. Therefore, using 1H-NMR quantitative analysis to detect trace characteristic peaks will easily present less accurate results, especially for the second repeating unit and / or the third repeating unit in the present application.
[0031] The aliphatic cycloalcohol residue of the present application is derived from an aliphatic cyclodiol; preferably, the aliphatic cycloalcohol residue is derived from an aliphatic cyclodiol having a boiling point of not less than 280° C. at room temperature and pressure. According to at least one embodiment of the present application, the aliphatic cycloalcohol residue comprises a structure of formula (iv): According to at least one embodiment of the present application, the aliphatic cycloalcohol residue comprises a structure of formula (v): According to at least one embodiment of the present application, the aliphatic cycloalcohol residue comprises a structure of formula (vi): In some embodiments, the aliphatic cyclic alcohol residue comprises a structure of formula (iv), a structure of formula (v), a structure of formula (vi), or a combination thereof; specifically, for example but not limited to, a structure of formula (iv), a structure of formula (v), or a structure of formula (vi), or a structure of formula (iv) and a structure of formula (v), or a structure of formula (iv), a structure of formula (v), and a structure of formula (vi). In some embodiments, the structure of formula (iv) is derived from, for example, isosorbide (hereinafter referred to as isosorbide), or a combination thereof; in some embodiments, the structure of formula (v) is derived from, for example, cyclohexanedimethanol (hereinafter referred to as CHDM), or a combination thereof; in some embodiments, the structure of formula (vi) is derived from, for example, tricyclodecanedimethanol (hereinafter referred to as TCDDM), or a combination thereof. According to at least one embodiment of the present application, the polyester of the present application is obtained by performing an esterification reaction or a transesterification reaction using the aliphatic cyclodiol as one of the reaction monomers and then performing polymerization.
[0032] According to a preferred embodiment of the present application, the aliphatic cyclic alcohol residue of the polyester comprises a structure of formula (iv). After analysis, the weight ratio of the second repeating unit to the third repeating unit of the polyester of the present application is 0.246 to 0.484. According to a preferred embodiment of the present application, the aliphatic cyclic alcohol residue of the polyester comprises a structure of formula (v). After aminolysis analysis, the weight ratio of the second repeating unit to the third repeating unit is 0.102 to 0.481. According to a preferred embodiment of the present application, the aliphatic cyclic alcohol residue of the polyester comprises a structure of formula (vi). After aminolysis analysis, the weight ratio of the second repeating unit to the third repeating unit is 0.164 to 0.484.
[0033] In some embodiments, the polyester of the present application has a glass transition temperature (T g ) is greater than or equal to 75°C, for example but not limited to 78°C, 84°C, 89°C, 90°C, 92°C, 93°C, 95°C, 96.1°C, 96.3°C, 109°C or 110°C, or any value within the range formed by any two of the above values. It is believed that when the polyester has a relatively high glass transition temperature, it can be considered that the heat resistance of the polyester is good.
[0034] In addition, the polyester of the present application may further contain other ingredients required for subsequent processing to form products to provide a wide range of properties, such as additives, modifiers or reinforcing agents, without detracting from the purpose of the present application; wherein the additives include, for example, stabilizers (such as ultraviolet absorbers), antioxidants, heat stabilizers, lubricants, mold release agents, catalyst deactivators, nucleating agents, crystallization accelerators, etc.
[0035] [Production method of polyester]
[0036] The preparation method of the polyester of the present application is not particularly limited. A person with ordinary knowledge in the field of the present application can select a suitable preparation method based on the disclosure of the present specification. For example, the polyester of the present application is prepared by "esterification repolymerization" or "transesterification (also known as ester exchange) repolymerization", which can be prepared by a method comprising the following steps: a diol and a dibasic acid (for esterification reaction) or a diol and a dibasic ester (for transesterification reaction) as reaction monomers are mixed with catalysts, co-catalysts, and thermal stabilizers and other additives as needed in a high-pressure reactor to form a mixture; the reaction monomers can be added once or in batches, and the number of batch additions is not limited in the present application. Under a condition of elevated temperature and elevated pressure and a stirring speed of, for example, 100 to 500 rpm, the mixture is mixed uniformly, and the monomers in the mixture are subjected to an esterification reaction or a transesterification reaction to generate oligomers (or oligomers). The elevated temperature condition may be, for example, room temperature to 180° C. or room temperature to 270° C., and the elevated pressure condition may be, for example, 0 standard atmosphere to 6 standard atmospheres, preferably 1 standard atmosphere to 4 standard atmospheres, wherein the reaction time of the esterification reaction or the transesterification reaction may be, for example, 2 to 6 hours or 1 to 6 hours to complete the reaction. Then, the mixture containing the oligomer is vacuum-evacuated to less than 3 torr, preferably 1 torr, under another elevated temperature condition, for example, 260° C. to 310° C., and a chain extender or a cross-linking agent may be added as needed, and the reaction time may be, for example, 1.5 to 8 hours to complete the polymerization reaction, i.e., to obtain polyester.
[0037] In some embodiments, the reaction status can be determined by observing the amount of alcohol or water produced in the temperature-raising esterification reaction. Specifically, through theoretical calculation, the theoretical amount of alcohol or water produced after all monomers in the mixture react can be obtained; when the amount of alcohol or water produced reaches 80wt.% or more of the theoretical amount of alcohol or water (for example, but not limited to 85wt.%, 90wt.% or 95wt.%), it indicates that the esterification reaction is completed, and the subsequent vacuum pumping step can be performed.
[0038] The catalyst, co-catalyst and thermal stabilizer can be added at the beginning of the reaction, and can also be added before vacuum pumping. The type of the catalyst is not particularly limited, and it can be, for example, but not limited to, titanium butoxide (Titanium (IV) butoxide), antimony trioxide (Sb2O3), antimony acetate (Sb(OAc)3), germanium dioxide (GeO2), titanium isopropoxide (Titanium (IV) isopropoxide), monobutyl tin tris (Butyltin tris (2-ethylhexanoate)) or a combination thereof. The type of the co-catalyst is not particularly limited, and it can be, for example, but not limited to, copper acetate, zinc acetate, magnesium acetate, sodium acetate, potassium acetate or a combination thereof. The type of the thermal stabilizer is not particularly limited, and it can be, for example, but not limited to, phosphoric acid, phosphorous acid, hypophosphorous acid and its salts, trimethyl phosphate (Trimethyl phosphate, TMP), triethyl phosphate (Triethyl phosphate, TEP), triphenyl phosphate (Triphenyl phosphate, TPP), 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, Bis(2,6-di-ter-butyl-4-methylphenyl)pentae The chain extender may be selected from the group consisting of 2,4-di-tert-butylphenyl, 2,4-di ...
[0039] In some embodiments, regarding the reactive monomers for preparing polyester, the diol monomers used in the present application may be specifically isosorbide, CHDM, TCDDM, ethylene glycol (EG), diethylene glycol (DEG) or a combination thereof; and the dibasic acid monomers used in the present application may be specifically terephthalic acid (PTA); in addition, the dibasic ester monomers or oligomers used in the present application may be specifically recycled PCR (Post-Consumer Recycled Plastic)-PET, bis-2-hydroxylethylterephthalate (BHET), ethylene glycol:terephthalate (3:2) or dimethyl terephthalate (DMT).
[0040] In a preferred embodiment, the polyester of the present application does not contain butanediol (BDO) and / or residues derived from BDO; in another more preferred embodiment, the polyester of the present application is PET.
[0041] In one embodiment of the present application, the polyester of the present application is prepared by a transesterification reaction of a recycled polyester. Specifically, the recycled polyester is aminolyzed into oligomers, which are then subjected to a transesterification reaction with the corresponding diols and polymerized; for example, BHET or ethylene glycol: terephthalic acid (3:2) obtained after degradation of the recycled polyester can be used as a raw material for subsequent reactions. The recycled polyester can be, for example, but not limited to, recycled polyethylene terephthalate (PET), poly trimethylene terephthalate (PTT), or polybutylene terephthalate (PBT); preferably, it is recycled PET or PBT; if recycled polyester is used, the advantages of polyester that conforms to environmental protection trends and meets the industry's requirements for dyeing ability and mechanical strength can be further achieved.
[0042] In addition, the polyester obtained by the above preparation method can be injection molded after pelletizing; wherein, before injection molding, the polyester pellets need to be dried to a moisture content of less than 200 ppm, preferably less than 100 ppm, and more preferably less than 50 ppm.
[0043] [Molding products]
[0044] The polyester of the present application can be formed into various molded products by molding methods known in the art to which the present application belongs and can be applied to various fields. The molded products include but are not limited to films, layer base films, sheets, plates, stretched sheets, monofilaments, multifilaments, non-woven fabrics, untwisted yarns, staple fibers, curly fibers, striped ribbons, composite fibers, foams or injection molded bodies. The polyester of the present application can be applied in fields including but not limited to food contact, automotive molds, commercial housewares, compound consumables, electronic products, device housings, in-store fixtures, electronic packaging materials, outdoor signs, personal care products, cosmetics packaging, textile and clothing, exercise apparatus, toys or bottles.
[0045] Example
[0046] Hereinafter, the present application will be further described with detailed description and specific embodiments. However, it should be understood that these specific embodiments are only used to help the present application to be more easily understood and are not used to limit the scope of the present application.
[0047] 1. Analytical methods
[0048] Here, the present application provides analysis and measurement methods of the polyesters of Examples 1 to 15 and Comparative Examples 1 to 11.
[0049] [ 1 H-NMR analysis] 1. Sample preparation: The polyester was dissolved in deuterated chloroform (CDCl3, purchased from Aldrich) to obtain a solution with a concentration of 5 mg / mL. 2. Analytical instrument: AVANCE-500NMR nuclear magnetic resonance instrument (purchased from BRUKER, Germany). 3. Analysis method: The resonance frequency is set to 500 MHz, the pulse width is 10 microseconds, the waiting time is 2 seconds, and the cumulative number is 32 times. After the sample solution is detected by the nuclear magnetic resonance instrument, the obtained signal is converted into a spectrum by Fourier transformation, and the signal of deuterated chloroform is set to 7.24 ppm.
[0050] [Aminolysis analysis] 1. Pre-analysis treatment: 5 g of polyester and 20 g of hydrazine (N2H4) solution (60 wt.% hydrazine and 40 wt.% water, purchased from Aldrich) were weighed and placed in a 50 mL conical flask, heated to boiling and refluxed (temperature of 110 to 120° C.) for 4 hours, wherein the hydrazine solution was used as a solvent and a reagent for degrading the polyester. After the polyester was completely decomposed, the temperature was lowered and the weight was weighed, and an internal standard of appropriate concentration was added (in this embodiment, a 1,6-hexanediol (HDO) aqueous solution with a concentration of 6000 ppm was used as the internal standard). After filtering with 5A filter paper to form a degradation solution, the degradation solution was injected into a gas chromatography (GC) and pure BHET was used as a standard to determine the outflow position of BHET. The BHET area of the degradation solution in the GC detection was further examined to be less than 0.01% of the total area. If the BHET area accounts for more than 0.01% of the total area, it means that the degradation reaction is not complete and the degradation reaction needs to be repeated. 2. Preparation of calibration curve: In this specific embodiment, the second repeating unit contained in the polyester is derived from diethylene glycol (DEG), which can also be called DEG residue; the third repeating unit is derived from EG, which can also be called EG residue. Therefore, five concentration gradients of DEG or EG are weighed and dissolved in hydrazine (N2H4) solution, wherein the five concentration gradients of DEG are 0.1wt.%, 0.3wt.%, 0.6wt.%, 1.2wt.% and 2.0wt.%, and the five concentration gradients of EG are 1wt.%, 3wt.%, 10wt.%, 15wt.% and 20wt.%, respectively. Equal amounts of internal standards with appropriate concentrations are added to the solutions of these five concentration gradients (in this embodiment, HDO aqueous solution with a concentration of 6000ppm is used as the internal standard), and after uniform mixing, The samples were injected into GC; nitrogen was used as the mobile phase, and a HP-1 column with a length of 50 m, an inner diameter of 0.32 mm, and a liquid film thickness of 1.05 μm was used. The injection temperature and the detection temperature were set to 280°C. The oven temperature was kept at 80°C for 3 minutes, then heated to 300°C at a heating rate of 20°C / min and kept at that temperature for 3 minutes. HDO was used as the internal standard. The relationship between the peak area ratio of DEG or EG and HDO and the concentration ratio of DEG or EG and HDO was linear, and the linear relationship between the GC peak area and concentration of DEG and EG was obtained, and the determination coefficient (R2 ) is greater than 0.99; based on this linear relationship, the concentrations of the DEG and EG residues of the polyester can be obtained.
[0051] [Glass transition temperature, T g )analyze] The glass transition temperature of the polyester was measured according to the standard method of ISO 3146 using a differential scanning calorimetry (DSC) analyzer (purchased from TA Instruments) and a thermal mechanical analyzer.
[0052] [Inherent viscosity (IV) analysis] The intrinsic viscosity of polyester was measured according to the standard method of ASTM D4603 using a dynamic viscosity tester (CRC-31L, purchased from Shunyi Instrument Co., Ltd.), and its unit is "deciliter / gram (dL / g)".
[0053] [Tensile elongation (TE) analysis] The tensile strength of polyester is measured according to the standard method of ISO 527 using a universal material testing machine (purchased from Instron Corporation), and its unit is “MPa”.
[0054] [Dyeability Analysis] 1. Standard method: Analyzed according to the standard method of ASTM D6290. 2. Sample preparation: The polyester was pelletized and then injection molded into a flat test piece of 100 mm*100 mm*3 mm. 1 wt.% of masterbatch was mixed into the piece during injection, and blue, black and red masterbatches were tested. 3. Analysis method: After the flat test piece is ejected, the "L*", "a*" and "b*" in the polyester color model (Lab) are tested at three random points on the flat test piece according to the standard method of ASTM D6290, and the average ΔE* between the three points is obtained. ab ; If ΔE* ab The smaller the value, the more uniform the color of the flat test piece. It is divided into four grades: excellent, good, medium and poor.
[0055] 2. Property Analysis of Example Polyester
[0056] [Examples 1 to 5 and Comparative Examples 1 to 4]
[0057] The polyesters of Examples 1 to 5 and Comparative Examples 1 to 4 were prepared and analyzed according to the preparation methods and analysis methods described above; and the details and properties of the polyesters including polyester formulation, process (manufacturing process) conditions, repeating unit content, glass transition temperature (T g ), intrinsic viscosity, tensile strength and dyeability analysis results are presented in Table 1. Referring to Table 1, the ethylene glycol, terephthalate (3:2) has the following structure: In addition, the residue of PTA is a repeating unit derived from PTA (in mol %, calculated based on the total molar number of repeating units derived from dibasic acid in the polyester); the residue of EG is a repeating unit derived from EG (in mol %, calculated based on the total molar number of repeating units derived from diol in the polyester); the structure of formula (vi) is a repeating unit derived from TCDDM (in mol %, calculated based on the total molar number of repeating units derived from diol in the polyester); the structure of formula (v) is a repeating unit derived from CHDM (in mol %, calculated based on the total molar number of repeating units derived from diol in the polyester); the residue of BDO is a repeating unit derived from BDO (in mol %, calculated based on the total molar number of repeating units derived from diol in the polyester).
[0058] Table 1
[0059] As shown in Table 1, the polyesters of Examples 1 to 5 of the present application have a suitable weight ratio of the second repeating unit / the third repeating unit, and thus have excellent heat resistance, as well as good tensile strength and dyeability. Without being limited by a particular theory, it is believed that the structure of formula (vi) is related to the heat resistance of the polyester. More specifically, when the polyester has the structure of formula (vi), it has a higher glass transition temperature and better heat resistance than the polyester without the structure of formula (vi). In particular, Examples 1 to 3 all contain the structure of formula (vi), so the polyesters of these Examples have relatively higher T g ; It can be seen from the corresponding basis that the weight ratio of the second repeating unit / the third repeating unit of the polyester in Comparative Example 1 is lower than the range requested in the present application, so although it has ideal heat resistance, it does not have good tensile strength.
[0060] Without being limited by a particular theory, it is believed that the structure of formula (v) is related to the tensile strength of the polyester; more specifically, when the structure of formula (v) is present, the tensile strength of the polyester is better. In particular, since both Examples 4 and 5 contain the structure of formula (v), the polyesters of these Examples have relatively better tensile strength; as can be seen from the comparative basis, the weight ratio of the second repeating unit / the third repeating unit of the polyester of Comparative Example 2 is also lower than the required range, and thus also has relatively poor tensile strength; moreover, due to the relatively higher content of the third repeating unit, its dyeability is also poor.
[0061] Comparative Example 3 has a BDO residue but does not have the structure of formula (v) or (iv), and the weight ratio of the second repeating unit / the third repeating unit of the polyester is lower than the required range, so it cannot have excellent heat resistance, tensile strength and dyeability.
[0062] Comparative Example 4 is a PET resin of the prior art, in which the weight ratio of the second repeating unit / the third repeating unit is lower than the required range, and Comparative Example 4 does not have the structure of formula (v) or formula (iv). From the data, Comparative Example 4 cannot have excellent heat resistance, tensile strength and dyeability.
[0063] [Examples 6 to 10 and Comparative Examples 5 to 7]
[0064] The polyesters of Examples 6 to 10 and Comparative Examples 5 to 7 were prepared and analyzed according to the preparation methods and analysis methods described above, and the details and properties of the polyesters including the polyester formulation, process conditions, repeating unit content, glass transition temperature (T g ), polymerization time, intrinsic viscosity, tensile strength and dyeability analysis results are presented in Table 2. Please refer to Table 2, both BHET are recycled monomer esters, while DMT is not a recycled ester. In addition, similar to the above embodiment, the PTA residue is derived from the repeating unit of PTA (in mole %, calculated based on the total mole number of repeating units derived from dibasic acids in the polyester); the EG residue is derived from the repeating unit of EG (in mole %, calculated based on the total mole number of repeating units derived from diols in the polyester); the structure of formula (vi) is derived from the repeating unit of TCDDM (in mole %, calculated based on the total mole number of repeating units derived from diols in the polyester); the residue of the structure of formula (v) is derived from the repeating unit of CHDM (in mole %, calculated based on the total mole number of repeating units derived from diols in the polyester); the structure of formula (iv) is derived from the repeating unit of lsosorbide (in mole %, calculated based on the total mole number of repeating units derived from diols in the polyester).
[0065] Table 2
[0066] As shown in Table 2, the polyesters of Examples 6 to 10 of the present application have a suitable weight ratio of the second repeating unit / the third repeating unit, and thus have excellent heat resistance, as well as good tensile strength and dyeability; in detail, Examples 6 to 7 all contain the structure of formula (vi) and the structure of formula (v), and Examples 8 to 10 all contain the structure of formula (v) and the structure of formula (iv). It can be seen from the corresponding comparison basis that the weight ratio of the second repeating unit / the third repeating unit of the polyesters of Comparative Examples 5 to 7 is lower than the range requested by the present application, so although they have ideal heat resistance, they do not have good tensile strength; at the same time, the dyeability performance of the polyesters of Examples 6 to 10 is also better than that of Comparative Examples 5 to 7. In addition, under the condition of a similar range of intrinsic viscosity, the polyesters of Examples 6 to 10 using recycled esters as reaction monomers have lower esterification time and polymerization time than the esterification time and polymerization time of Comparative Examples 5 to 7 which do not use recycled esters as reaction monomers, which is beneficial to shortening production time and increasing production efficiency.
[0067] [Examples 11 to 15 and Comparative Examples 8 to 11]
[0068] The polyesters of Examples 11 to 15 and Comparative Examples 8 to 11 were prepared and analyzed according to the preparation methods and analysis methods described above, and the details and properties of the polyesters including the polyester formulation, process conditions, repeating unit content, glass transition temperature (T g ), intrinsic viscosity, tensile strength and dyeability analysis results are presented in Table 3. Similar to the above examples, PTA residues are repeating units derived from PTA (in mole %, calculated based on the total mole number of repeating units derived from dibasic acids in the polyester); EG residues are repeating units derived from EG (in mole %, calculated based on the total mole number of repeating units derived from diols in the polyester); formula (vi) structure is a repeating unit derived from TCDDM (in mole %, calculated based on the total mole number of repeating units derived from diols in the polyester); formula (v) structure is a repeating unit derived from CHDM (in mole %, calculated based on the total mole number of repeating units derived from diols in the polyester); formula (iv) structure is a repeating unit derived from lsosorbide (in mole %, calculated based on the total mole number of repeating units derived from diols in the polyester).
[0069] Table 3
[0070] As shown in Table 3, Examples 11 to 15 of the present application have a suitable weight ratio of the second repeating unit / the third repeating unit, and thus have excellent heat resistance, as well as good tensile strength and dyeability. Specifically, Examples 11 to 13 all contain the structure of formula (vi) and the structure of formula (iv), while Example 14 contains the structure of formula (v), and Example 15 contains the structure of formula (vi). Based on the corresponding comparison basis, it can be seen that the weight ratio of the second repeating unit / the third repeating unit of the polyester of Comparative Examples 8, 10 and 11 is lower than the range requested by the present application, so although they have ideal heat resistance, they do not have good tensile strength; at the same time, the dyeability performance of the polyester of Examples 11 to 15 is also better than that of Comparative Examples 8 to 10 and 11. On the other hand, the weight ratio of the second repeating unit / the third repeating unit of the polyester of Comparative Example 9 is higher than the range requested by the present application, which is believed to indicate that the degree of polymerization is insufficient and the molecular weight is too low, and it is impossible to have excellent tensile strength, resulting in a decrease in its mechanical value.
[0071] 3. Ammonolysis analysis and 1 Differences in H-NMR analysis
[0072] According to the above mentioned aminolysis analysis and 1 The H-NMR analysis method was used to analyze the polyesters of Example 14 and Comparative Example 6 of the present application, and the analysis results of the weight ratio of the second repeating unit / the third repeating unit of the polyesters are presented in Table 4.
[0073] Table 4
[0074] As shown in Table 4, the weight ratio of the second repeating unit / the third repeating unit of Example 14 is 0.102 according to the result of aminolysis analysis, while 1 The result of H-NMR analysis was 0.089, with a 12.7% error between the two. The weight ratio of the second repeating unit / third repeating unit of Comparative Example 6 was 0.047 by aminolysis analysis and 0.061 by 1 The H-NMR analysis is 0.102, and there is a 117% error between the two. 1 The quantitative results of the second and third repeating units analyzed by H-NMR have large errors. This result fully demonstrates that the aminolysis analysis used in this application is more accurate than that of 1 H-NMR analysis can more accurately quantify the second and third repeating units in polyester.
[0075] In summary, the polyester of the present application has ideal heat resistance as well as good dyeing ability and mechanical strength. In addition, when recycled polyester is used as raw material, the purpose of producing polyester that meets the needs of the industry can be further achieved while complying with environmental protection trends.
[0076] In the present application, all ranges provided are intended to include each specific range within a given range and a combination of sub-ranges between the given ranges. In addition, unless otherwise stated, all ranges provided in the present application include the endpoints of the range. Thus, ranges 1 to 5 specifically include 1, 2, 3, 4 and 5, and sub-ranges such as 2 to 5, 3 to 5, 2 to 3, 2 to 4, 1 to 4, etc.
[0077] All publications and patent applications cited in this specification are incorporated herein by reference, and each individual publication or patent application is expressly and individually indicated to be incorporated by reference into this application for any and all purposes. In the event of any inconsistency between this application and any publication or patent application incorporated by reference into this application, this application controls.
Claims
1. A polyester comprising: The first repeating unit is represented by the following formula (i): in, R1 is C6 to C 16 Aromatic hydrocarbon groups; and A repeating unit derived from a diol, wherein the repeating unit derived from the diol comprises a second repeating unit, a third repeating unit and an aliphatic cycloalcohol residue; wherein the second repeating unit is represented by the following formula (ii), and the third repeating unit is represented by the following formula (iii): * indicates a connection key; Furthermore, according to aminolysis analysis of the polyester, a weight ratio of the second repeating unit to the third repeating unit is 0.100 to 0.
490.
2. The polyester according to claim 1, wherein the aliphatic cycloalcohol residue is derived from an aliphatic cyclodiol having a boiling point of not less than 280°C at normal temperature and pressure.
3. The polyester of claim 1, wherein the aliphatic cyclic alcohol residue comprises an isosorbide residue, a cyclohexanedimethanol residue, a tricyclodecane dimethanol residue, or a combination thereof.
4. The polyester of claim 1, wherein a weight ratio of the second repeating unit to the third repeating unit is 0.100 to 0.
484.
5. The polyester of claim 1, wherein the aliphatic cyclic alcohol residue comprises a structure of formula (iv): * indicates a connection key.
6. The polyester of claim 5, wherein a weight ratio of the second repeating unit to the third repeating unit is 0.246 to 0.
484.
7. The polyester of claim 1, wherein the aliphatic cyclic alcohol residue comprises a structure of formula (v): * indicates a connection key.
8. The polyester according to claim 7, wherein a weight ratio of the second repeating unit to the third repeating unit is 0.102 to 0.
481.
9. The polyester of claim 1, wherein the aliphatic cyclic alcohol residue comprises a structure of formula (vi): * indicates a connection key.
10. The polyester of claim 9, wherein a weight ratio of the second repeating unit to the third repeating unit is 0.164 to 0.
484.
11. The polyester of claim 1, wherein the content of the second repeating unit is no more than 3 wt.% based on the total weight of the polyester.
12. The polyester according to claim 1, having a glass transition temperature (T g ) is greater than 90°C.
13. The polyester as claimed in claim 1, which is prepared by a transesterification reaction of a recycled polyester. 。 14. A molded article formed from the polyester according to any one of claims 1 to 13.